Management Privacy dalam Penggunaan Fitur â€œClose Friendâ€ di Instagram - Dianiya, Vicky (Jurnal Studi Komunikasi, 2021)
Social media is basically to share information and self-disclosures by the account owner. However, there is an attitude of caution in expressing which must also be considered and needs to be considered. Technological developments make more and more new features appear on various social media platforms, one of them is the close friend feature on Instagram that can be used to limit users in sharing information that is considered more privacy. This study uses the Communication Privacy Management theory as a framework for investigating how Instagram users, especially young adults, use and respond to the use of the close friend feature. Overall, the results of interviews with five informants found evidence of five basic assumptions in using CPM implied on social media and showed that there is confidence in the disclosure of privacy when using the close friend feature.